2012
DOI: 10.1016/j.ceca.2011.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of calcium carriers and of the vacuole in the glucose-induced calcium signaling and activation of the plasma membrane H+-ATPase in Saccharomyces cerevisiae cells

Abstract: Previous work from our laboratories demonstrated that the sugar-induced activation of plasma membrane H(+)-ATPase in Saccharomyces cerevisiae is dependent on calcium metabolism with the contribution of calcium influx from external medium. Our results demonstrate that a glucose-induced calcium (GIC) transporter, a new and still unidentified calcium carrier, sensitive to nifedipine and gadolinium and activated by glucose addition, seems to be partially involved in the glucose-induced activation of the plasma mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…The Yeast Vacuolar Channel, Yvc1, is a homolog of the constitutively active inwardly rectifying calcium channels in mammals known as TRP (Transient Receptor Potential) channels, and likely represents a calcium-activated calcium channel, which has been shown to release Ca 2+ from the vacuole into the cytosol in response to hyperosmotic shock both by mechanical activation and Ca 2+ -induced calcium release [37]. Furthermore, a role was previously proposed for Yvc1 in glucose refeeding-induced calcium signaling [38].…”
Section: Involvement Of Other Known Calcium Transporters In Hts-inducmentioning
confidence: 95%
“…The Yeast Vacuolar Channel, Yvc1, is a homolog of the constitutively active inwardly rectifying calcium channels in mammals known as TRP (Transient Receptor Potential) channels, and likely represents a calcium-activated calcium channel, which has been shown to release Ca 2+ from the vacuole into the cytosol in response to hyperosmotic shock both by mechanical activation and Ca 2+ -induced calcium release [37]. Furthermore, a role was previously proposed for Yvc1 in glucose refeeding-induced calcium signaling [38].…”
Section: Involvement Of Other Known Calcium Transporters In Hts-inducmentioning
confidence: 95%
“…Further studies showed that the Yvc1-encoded channel is mechanosensitive, suggesting that vacuolar shrinkage during osmotic shock may directly activate the channel (Zhou et al 2003). Yvc1 is also thought to contribute to Ca 2+ transients observed after glucose readdition to starved cells (Bouillet et al 2012), although the mechanism of its activation is unknown.…”
Section: Ca 2+ Release From Intracellular Compartmentsmentioning
confidence: 99%
“…Ptk2 and Hrk1, members of the Npr1 family of protein kinases, which regulates multiple membrane transporters, are thought to phosphorylate Pma1 (Goossens et al 2000;Eraso et al 2006), and it may be dephosphorylated by a PP1-type phosphatase, containing the Glc7 catalytic subunit (Williams-Hart et al 2002). Other studies suggest that Ca 2+ -dependent signaling also contributes to activation of Pma1, by unknown mechanisms, in response to glucose addition (Tropia et al 2006;Bouillet et al 2012).…”
Section: Regulation Of Pma1mentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the absence of Ybt1 from a putative trimeric complex could destabilize the Pmc1-Nyv1 interaction and lead to facile trans-SNARE pairing and more efficient fusion. Others have found that Pmc1 and Yvc1 are both required for the uptake of extracellular Ca 2C during glucose induced Ca 2C signaling, 67 suggesting that the intake and efflux of vacuolar Ca 2C is interdependent. Yvc1 is a homolog of the TRPC family, which can be regulated through mechanical and osmotic stress.…”
mentioning
confidence: 99%